2023
DOI: 10.3389/fnagi.2023.1187684
|View full text |Cite
|
Sign up to set email alerts
|

Iron accumulation in the ventral tegmental area in Parkinson's disease

Abstract: IntroductionThe ventral tegmental area (VTA) is less affected compared to substantia nigra pars compacta (SNc) in Parkinson's disease (PD). This study aimed to quantitatively evaluate iron content in the VTA across different stages of PD in order to help explain the selective loss of dopamine neurons in PD.MethodsQuantitative susceptibility mapping (QSM) data were obtained from 101 PD patients, 35 idiopathic rapid eye movement sleep behavior disorder (RBD) patients, and 62 healthy controls (HCs). The mean QSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Zhang et al revealed that during the prodromal and early clinical stages of PD, there is no observable augmentation in iron accumulation within the ventral tegmental area. However, iron deposition exhibits a substantial increase as PD progresses into more severe stages (Zhang et al 2023a ). A two-year follow-up study indicated a negative correlation between iron deposition and dopamine transporters in early PD patients (Biondetti et al 2021 ).…”
Section: Iron Deposition In Pd Patientsmentioning
confidence: 99%
“…Zhang et al revealed that during the prodromal and early clinical stages of PD, there is no observable augmentation in iron accumulation within the ventral tegmental area. However, iron deposition exhibits a substantial increase as PD progresses into more severe stages (Zhang et al 2023a ). A two-year follow-up study indicated a negative correlation between iron deposition and dopamine transporters in early PD patients (Biondetti et al 2021 ).…”
Section: Iron Deposition In Pd Patientsmentioning
confidence: 99%
“…A study carried out with 101 patients with Parkinson's disease with quantitative susceptibility mapping data concluded that the ventral tegmental area does not show a significant increase in iron during pre-motor symptoms but that it significantly increases when the disease progresses [43]. Alpha lipoic acid, an iron chelating agent and antioxidant, decreases motor deficiencies in a Parkinson's animal model, and increases ferritin heavy chain 1 and ferroportin expression while decreasing divalent metal transporter 1 expression.…”
Section: Iron and Parkinson's Diseasementioning
confidence: 99%